2017
DOI: 10.1073/pnas.1704009114
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of immune chemoreceptors into sensors of the outside world

Abstract: Changes in gene expression patterns represent an essential source of evolutionary innovation. A striking case of neofunctionalization is the acquisition of neuronal specificity by immune formyl peptide receptors (Fprs). In mammals, Fprs are expressed by immune cells, where they detect pathogenic and inflammatory chemical cues. In rodents, these receptors are also expressed by sensory neurons of the vomeronasal organ, an olfactory structure mediating innate avoidance behaviors. Here we show that two gene shuffl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…the opposite phenotype of AnxA1 tg mice. Putting everything together, FPR may represent a prototype of signalling molecules that influence the behaviour of the host at both cellular and physical levels with the ultimate goal of preserving it from the challenges of the external environments 81 .…”
Section: Discussionmentioning
confidence: 99%
“…the opposite phenotype of AnxA1 tg mice. Putting everything together, FPR may represent a prototype of signalling molecules that influence the behaviour of the host at both cellular and physical levels with the ultimate goal of preserving it from the challenges of the external environments 81 .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of primates also benefit from a third FPR gene, termed FPR3 (also known as FPRL2 ). Phylogenetic analyses of immune mammalian FPR genes revealed that a first duplication led to the divergence of FPR1 and FPR2 and that a second duplication of FPR2 early in primate evolution led to FPR3 (Dietschi et al 2017 ; Liberles et al 2009 ; Migeotte et al 2006 ; Muto et al 2015 ). The ligand specificity of immune FPRs seems to be conserved among species.…”
Section: Expression and Function Of Fprs In The Immune Systemmentioning
confidence: 99%
“…The FPRs are another family of olfactory neurons expressed by localized VNO neurons [63,83]. Interestingly, FPR olfactory expression is restricted to rodents [84], and expression of these receptors occurs in a punctate and monogenic pattern in the VSNs [83], which is characteristic of the transcription of olfactory chemoreceptor genes [85]. Within the vomeronasal (VN) epithelium, Fpr-rs3, -rs4, -rs6 and -rs7 are transcribed by neurons in the apical zone, coincident with V1Rs, while Fpr-rs1 is transcribed by neurons in the basal zone, coincident with V2Rs [83].…”
Section: Genetic Regulation In the Vomeronasal Systemmentioning
confidence: 99%